Pendidikan Karakter Disiplin di Sekolah Dasar Negeri Kubang Laban, Kabupaten Serang - Rizkiya Aji; Desty Subroto; Riska Auliya; Novia Amanda; Meira Elsi Adista (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
character has an important role in forming students' personalities from an early age, especially at elementary school level. One of the main character values ​​that needs to be instilled is discipline education, which is the basis for forming a responsible and orderly attitude in everyday life. This research aims to examine the implementation of disciplined character education in elementary schools as well as the factors that support and hinder its implementation. The method used is qualitative research with the aim of exploring, studying and describing the implementation of character education in elementary schools. Data was collected through observation, interviews with teachers. And data on all students of SDN KUBANG LABAN SERANG DISTRICT, totaling 40 students consisting of 20 male students and 20 female students who have different characters and SDN KUBANG LABAN SERANG DISTRICT has rules and regulations where the rules must be carried out by female students. The results of the research show that disciplined character education can be incorporated into the educational process effectively (successfully achieving goals) through habituation activities, teacher example, and rules. However, the implementation of character education also faces obstacles such as lack of parental involvement. application outside the school environment. This research recommends the need for synergy between schools and teachers to instill disciplinary character on an ongoing basis.